Association of vascular endothelial growth factor levels in CSF and cerebral glucose metabolism across the Alzheimer's disease spectrum. (20th November 2018) - Wang, Zhaowei; Zhou, Wenjun; Zhou, Bo; Zhang, Jie; ,
Highlights: There were no significant differences in CSF VEGF levels in the NC, MCI and AD groups. CSF VEGF levels were positively associated with cerebral glucose metabolism. VEGF may have important implications for developing disease-modifying therapies for AD. Abstract: The association of vascular endothelial growth factor (VEGF) levels in CSF and cerebral glucose metabolism across the Alzheimer's disease (AD) spectrum is unclear. CSF VEGF levels were cross-sectionally related to cerebral glucose metabolism, as measured by 18F-fluorodeoxyglucose positron emission tomography (FDG-PET), using linear regression models. We found that VEGF levels were associated with cerebral glucose metabolism in patients with mild cognitive impairment (MCI) and AD, but not in cognitively normal older adults. Our data indicated that VEGF may play an important role in cerebral glucose metabolism.